(untitled) (Texas Journal of Medical Science, 2023)
The results of treatment of 171 elderly and senile patients with complicated forms of GCB are presented. Stage surgical treatment, taking into account the developed criteria for assessing the severity of the patient’s condition and the projected risk of developing postoperative complications using preliminary minimally invasive decompression interventions on the biliary tract performed in 42.2% of patients of the main group, made it possible to stop purulent-cholemic intoxication, improve the results of subsequent radical operations. In 15.6% of patients, these interventions were the final method of treatment. The priority staged use of minimally invasive interventions significantly reduced mortality, postoperative purulent-septic and extra-abdominal complications (3.1%, 12.4% and 29.9%, respectively), while in the comparison group these indicators were 8.1%, 32.4% and 41.9%.